Application of Sacrificial Coatings and Effect of Composition on Al-Al3Ni Ultrafine Eutectic Formation - Čelko, Ladislav; Klakurková, Lenka; Smetana, Bedřich; Slámečka, Karel; Žaludová, Monika; Hui, David; Švejcar, Jiří (Journal of Mining and Metallurgy, Section B: Metallurgy, 2014)
This paper introduces an unconventional method designed for forming hypereutectic alloys via coating deposition onto the substrate surface and subsequent heat treatment of such systems. The coating was produced from 99.7 wt.% nickel powder by means of high velocity oxyfuel (HVOF) spraying onto the surface of 99.999 wt.% aluminium sheet. The specimens were manufactured immediately after the spraying. Specimens were heat-treated using a differential thermal analysis (DTA) apparatus up to a temperature of 900 °C and then cooled down to the room temperature in argon atmosphere with constant heating and cooling rates, under which the Al-Ni intermetallic phase formed within the initial substrate. Two different alloy microstructures consisting of a coarse eutectic and an ultrafine well-dispersed eutectic were produced. The formation processes and resultant microstructures were studied by means of differential thermal analysis, metallography, scanning electron microscopy, energy dispersive microanalysis, and image analysis techniques.